2023
DOI: 10.1007/s12011-023-03870-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Valine Chelated Zinc Supplementation on Growth Performance, Antioxidant Capacity, Immunity, and Intestine Health in Weaned Piglets

Tuan Zhang,
Nan Zhang,
Shuyu Peng
et al.

Abstract: This study was conducted to investigate the effects of dietary valine chelated zinc (ZnVal) supplementation on growth performance, antioxidant capacity, immunity, and intestine health in weaned piglets. A total of 240 healthy 35-day-old weaned piglets (Duroc × Landrace × Yorkshire, average weight 10.70 ± 0.14 kg) were randomly divided into five groups with six replicate pens and eight piglets per pen. Dietary treatments were a corn–soybean meal basal diet supplemented with 0, 25, 50, 75, and 100 mg/kg ZnVal, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…MDA, one of the final products of polyunsaturated fatty acid peroxidation, is the most commonly known product, whose levels can directly reflect the lipid oxidative injury and can be regarded as a reliable marker of antioxidant status [ 28 , 31 ]. Previous studies have reported that different Zn sources (different concentrations) increased the activities of SOD, GPx and T-AOC and reduced the level of MDA, and further influenced the antioxidant status of piglets [ 15 , 18 , 25 , 27 , 32 ]. In line with the previous literature, our results also showed that ZnO and saZnO supplementation significantly increased the activity of T-AOC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MDA, one of the final products of polyunsaturated fatty acid peroxidation, is the most commonly known product, whose levels can directly reflect the lipid oxidative injury and can be regarded as a reliable marker of antioxidant status [ 28 , 31 ]. Previous studies have reported that different Zn sources (different concentrations) increased the activities of SOD, GPx and T-AOC and reduced the level of MDA, and further influenced the antioxidant status of piglets [ 15 , 18 , 25 , 27 , 32 ]. In line with the previous literature, our results also showed that ZnO and saZnO supplementation significantly increased the activity of T-AOC.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 17 ] reported that hydrolysable tannins (HT) + ZnO supplementation significantly improve the levels of IgM and IgA in serum compared with the CON group. Peng et al [ 34 ] and Zhang et al [ 32 ] showed that porous ZnO and valine-chelated Zn (ZnVal) increased serum IgG. Another study also indicated that ZnO and nano-ZnO increased the serum concentration of IgA and decreased the concentration of IgM, but had no impact on IgG [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation